2017
DOI: 10.1111/bjh.14951
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of adults and children with primary mediastinal B‐cell lymphoma treated with dose‐adjusted EPOCH‐R

Abstract: Treatment with dose-adjusted EPOCH (etoposide, doxorubicin, cyclophosphamide, vincristine, prednisone) chemotherapy and rituximab (DA-EPOCH-R) has become the standard of care for primary mediastinal B-cell lymphoma (PMBCL) at many institutions despite limited data in the multi-centre setting. We report a large, multi-centre retrospective analysis of children and adults with PMBCL treated with DA-EPOCH-R to characterize outcomes and evaluate prognostic factors. We assessed 156 patients with PMBCL treated with D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 28 publications
(31 reference statements)
6
98
2
2
Order By: Relevance
“…A retrospective study in 2017 supported these results when it reported on 156 adults and children with PMBCL who received DA‐EPOCH‐R. The estimated 3‐year EFS was 85·9% (95% CI 80·3–91·5%) and OS 95·4% (95% CI 91·8–99·0%); there were no differences in outcomes between adults and children (Giulino‐Roth et al , ). In this study, 14·9% patients received RT.…”
Section: Current First‐line Treatmentmentioning
confidence: 87%
“…A retrospective study in 2017 supported these results when it reported on 156 adults and children with PMBCL who received DA‐EPOCH‐R. The estimated 3‐year EFS was 85·9% (95% CI 80·3–91·5%) and OS 95·4% (95% CI 91·8–99·0%); there were no differences in outcomes between adults and children (Giulino‐Roth et al , ). In this study, 14·9% patients received RT.…”
Section: Current First‐line Treatmentmentioning
confidence: 87%
“…These results have appeared also in other studies. 12,13,[26][27][28][29] There was one, however, where the outcome in patients treated with R-CHOP was poor. 22 Surprisingly, we observed a trend toward an increased relapse rate after an initial DA-EPOCH-R treatment compared to R-CHOP.…”
Section: Response Assessment and Survival Analysismentioning
confidence: 99%
“…PMBCL patients had worse outcomes compared to other DLBCL patients [33,34]. Recently, the efficacy of rituximab in pediatric PMBCL patients has been reported [35,36]. We included five PMBCL patients, of which two showed recurrence.…”
Section: Discussionmentioning
confidence: 99%